The Effect of Sports and Physical Activity on Elderly Reaction Time and Response Time - Abdolrahman Khezri; Elahe Arab Ameri; Rasoul Hemayattalab; Ronak Ebrahimi (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: Physical activities ameliorate elderly motor and cognitive performance. The aim of this research is to study the effect of sport and physical activity on elderly reaction time and response time. Methods & Materials: The research method is causal-comparative and its statistical population consists of 60 active and non-active old males over 60 years residing at Mahabad city. Reaction time was measured by reaction timer apparatus, made in Takei Company (YB1000 model). Response time was measured via Nelson’s Choice- Response Movement Test. At first, reaction time and then response time was measured. For data analysis, descriptive statistic, K-S Test and One Sample T Test were used Results K-S Test show that research data was parametric. According to the results of this research, physical activity affected reaction time and response time. Results: of T test show that reaction time (P=0.000) and response time (P=0.000) of active group was statistically shorter than non- active group. Conclusion: The result of current study demonstrate that sport and physical activity, decrease reaction and response time via psychomotor and physiological positive changes.